Towards a common vision: Pulling together or apart? A review of sub-national patterns of multiple deprivation in Namibia - Ojijo Odhiambo (International Policy Centre for Inclusive Growth (IPC-IG), 2012)
This paper presents a review of deprivation at the sub-national (regional) level in Namibia in the material, employment, health, education, services and housing domains as well as constituency-level multiple deprivation, but aggregated at regional levels. The study provides a strong basis for interrogating the reasons for the existence of the wide inter- and intraregional inequality and inequity with respect to levels of income and access to basic services and identifying priority sectors, at the sub-national level, for public investments. Further, the study provides a useful basis for initiating public policy discourse with regard to resource allocation and, most importantly, ring fencing and targeting those resources to areas or sectors where the particular regions are most deprived and linking development to the exercise of political and other forms of leadership, and accountability for results and impact at the lowest possible level. Another possible contribution of this study could be the need for policy- and decisionmakers in Namibia to consider institutionalising the Namibia Index of Multiple Deprivationweighted Equalization Fund (NIMDEF), whereby regions - and subsequently constituencies - receive and apply development funds and other resources on the basis of the relative weights of their index of multiple deprivation and population sizes. The study is a useful addition to the existing collection of proposals for consideration by policy- and decision-makers to put the country on a new development pathway as it moves towards a green economy.
Keywords: 330; inequality; multiple deprivation; multiple deprivation-weighted index equalization fund; green economy